COMMENT ON “OPTIMAL SHELF-SPACE STOCKING POLICY USING STOCHASTIC DOMINANCE UNDER SUPPLY-DRIVEN DEMAND UNCERTAINTY” - Saffari, Mohammad (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
The paper authored by Amit et al. [Amit, R. K., Mehta, P., & Tripathi, R. R. “Optimal shelf-space stocking policy using stochastic dominance under supply-driven demand uncertainty”, European Journal of Operational Research, 246(1), pp. 339-342 (2015)] proposes a newsvendor model in which demand depends on displayed inventory. Under stochastic dominance conditions, they claimed that the profit function is concave at its extremum points. In the present study, it is expressed that this statement is not generally precise.